PHARMACOKINETIC AND PHARMACODYNAMIC OF MATRIX-TYPE QUININE PATCH USING COSOLVENT TO ENCHANCE WATER SOLUBILITY - Fauzan Triandi, Muhammad
Leg cramp is defined as spasticity, shortening, feeling stuck, or the tension on the leg muscles. Leg cramp that occur when sleeping at night called as nocturnal leg cramps. Matrix-type transdermal quinine patch has been developed in previous studies with increasing the solubility of quinine in water to produce a rational size of the patch that could be used in humans and provide a minimum dose of quinine for anti-cramp effect. Reformulated quinine patch produced good film characteristics with a relatively constant in-vivo release up to 20 h. The reformulated quinine patch is expected to optimally provide anti-cramp effect in a desired duration with a better safety compared to oral quinine. The purpose of this study was to evaluate the reformulated quinine patch by determining the pharmacokinetic profile for an extended time, determining theoharmacodynamic profile of anti-cramp effect, and determining the safety of quinine patch for multiple dose application. Matrix-type quinine patch (200 mg/28.26 cm2) was prepared from quinine gel (6.67%) by dissolving quinine HCI in water: ethanol (5:4) in the basis of HPMC (9%) then dried to form film. Pharmacokinetic study was performed in one group (n=5) with administration of the quinine patch dose of 18 mg/kg BW for 72 h. Pharmacodynamic study for 2 days was performed in two groups i.e. normal group without application of the patch and test group with quinine patch doses of 18 mg/kg BW, using the rotarod method (n=6) and Weight-loaded Forced Swimming Test (WFST) method (n=5). Safety of quinine patch was evaluated in the two same y•oups (n=7) by determining the blood profiles for 4 weeks of patch application. Phannacokinetic profiles of matrix-type quinine patch showed AUCo-72 (n=5) of 5834,55 ± 598,15 ng.h/mL, tmax at 8 hours and Cmax of 174,18 16,06 ng/mL (n=5). Pharmacokinetic study showed C values which were not statistically different with previous studies (p> 0.05) with a relatively constant concenfration within the therapeutic range up to 56 h. Pharmacodynamic evaluation with rotarod method showed anti-cramp effectiveness which was maintained until the 27th h. Blood profile after 4 weeks of patch application showed no significant change in red blood from beginning until 4 weeks application. Other blood parameters did not change significantly (p>O.05) compared to the normal group. These results showed a good safety of the use of reformulated quinine patch. Quinine patch produced by increase in quinine solubility achieved plasma effective concentration which maintained within the terapeutic range up to 56 h, with anti-cramp effect attained until the 27th h, and the safety shourn from the blood profiles for 4 weeks use of the patch.